Clinical characteristics, risk factors, and outcome of tuberculosis in kidney transplant recipients: A multicentric case‐control study in a low‐endemic area. Issue 5 (28th June 2018) - Gras, Julien; De Castro, Nathalie; Montlahuc, Claire; Champion, Laure; Scemla, Anne; Matignon, Marie; Lachâtre, Marie; Raskine, Laurent; Grall, Nathalie; Peraldi, Marie Noëlle; Molina, Jean Michel
Abstract: Objectives: Tuberculosis (TB) is a rare but life‐threatening infection after solid organ transplant. The present study was undertaken to assess the clinical features, risk factors, and outcome of TB after kidney transplantation in a low‐prevalence area. Methods: We conducted a retrospective study, describing all kidney transplant recipients diagnosed with TB between 2005 and 2015 in 3 French centers. For each TB case, 2 controls without TB were identified and matched by center, age, transplant date, and birth country. Risk factors associated with TB were identified and survival estimated. Results: Thirty‐two cases and 64 control patients were included among 3974 transplantations. The prevalence of TB was 0.83%. Median age at the time of diagnosis was 64 years; 75% were born in a high TB prevalence country, but only 3 had received isoniazid prophylaxis for latent TB infection. TB occurred at a median of 22 months after transplantation. On diagnosis, 66% had disseminated infection. Median duration of treatment was 9 months. Immunosuppressive therapy changes were necessary in all patients because of drug‐drug interactions. Among cases, 5 deaths occurred during follow‐up (median duration: 41 months), one directly related with TB. Survival was significantly lower in transplant recipients with TB, as compared to controls ( P  = .001). No predictive factors of tuberculosis after transplantation were statistically significant in univariate analysis. Conclusion: TB in kidney transplant recipients is a rare and late event, but is associated with significantly reduced survival. Our results emphasize the need for systematic screening for LTBI, followed by IPT in high‐risk patients.